As feminilidades: signos de consumo e a identificação das mulheres com a capa da Revista Elle Brasil - Cuch, Renata Cabral (2016)
This research seeks, from considerations freudian-lacanian about the concept of identification, understanding the mental processes regarding the femininity of women-readers, when in contact with the sign elements arranged on the covers of Elle Brazil magazine. The research is grounded on the assumption that such cases mobilize the attention of readers by offering images of top models that apparently holds "all that remains", thus promoting an object displacement effect that is at the service of desire. In addition to demonstrating the existence of signic devices that can operate as an object of desire from the identification processes, the work makes a brief distinction between femininity in psychoanalysis and female model presented by the media universe. It also aims to demystify the use of the mask as an intrinsic device to the female and produce a psychoanalytical semiotic analysis of verbal-visual messages mediated by the consumption of the signs on the covers. The research was conducted, first, by the extraction of signic artifices of messages of the covers and subsequently by psychoanalytic reading of these signs. The corpus consists of four editions of Elle magazine in Brazil, collected interchangeably over the years 2014 and 2015. To achieve the objectives were articulated the concepts of "mask" presented initially by Joan Rivière and borrowed by Jacques Lacan in his research on the dynamics of femininity mechanisms; the concepts of the theory of signs produced by the semiotics of Charles Sanders Peirce, they are here expressed through the eyes of Lucia Santaella; besides the considerations of Slavoj Žižek about ideological mechanisms and meaningful representations from the experience process of the readers with the media offers. It is believed that these mechanisms can be articulated with intrapsychic dynamics that operate in the way phallic traits influence women choices. This research suggests that the messages displayed in Elle Brazil magazine covers can raise the women-readers unconscious starting from the offerings of objects, filling the gap that operates in femininity. Therefore, the mask concepts, veil and face were used in an attempt to understand the identification modes